A Comprehensive Analysis of Tobacco Smoking History as a Risk for Outcomes after Endoscopic Transsphenoidal Resection of Pituitary Adenoma - Min, Susie; Zhang, Grace; Hu, Alex; Petito, Gabrielle T.; Tripathi, Siddhant H.; Shukla, Geet; Kumar, Adithya; Shah, Sanjit; Phillips, Katie M.; Forbes, Jonathan A.; Zuccarello, Mario; Andaluz, Norberto O.; Sedaghat, Ahmad R. (Journal of Neurological Surgery Part B: Skull Base, 2023)
Objectives This study seeks to comprehensively analyze the impact of smoking history on outcomes after endoscopic transsphenoidal hypophysectomy (TSH) for pituitary adenoma.Design This was a retrospective study.Setting This study was done at the tertiary care center.Participants Three hundred and ninety-eight adult patients undergoing TSH for a pituitary adenoma.Main Outcome Measures Clinical and tumor characteristics and operative factors were collected. Patients were categorized as never, former, or active smokers, and the pack-years of smoking history was collected. Years since cessation of smoking was obtained for former smokers. Specific outcomes included postoperative cerebrospinal fluid (CSF) leak, length of hospitalization, 30-day return to the operating room, and 30-day readmission. Smoking history details were comprehensively analyzed for association with outcomes.Results Any history of smoking tobacco was associated with return to the operating room (odds ratio [OR] = 2.67, 95% confidence interval [CI]: 1.05–6.76, p = 0.039), which was for persistent CSF leak in 58.3%. Among patients with postoperative CSF leak, any history of smoking was associated with need for return to the operating room to repair the CSF leak (OR = 5.25, 95% CI: 1.07–25.79, p = 0.041). Pack-years of smoking was positively associated with a return to the operating room (OR = 1.03, 95% CI: 1.01–1.06, p = 0.048). In all multivariable models, all negative outcomes were significantly associated with the covariate: occurrence of intraoperative CSF leak.Conclusion This is the first study to show smoking may have a negative impact on healing of CSF leak repairs after TSH, requiring a return to the operating room. This effect appears to be dose dependent on the smoking history. Secondarily, intraoperative CSF leak as covariate in multivariable models was significantly associated with all negative outcomes.
Keywords: smoking; transsphenoidal hypophysectomy; pituitary adenoma; complications; cerebrospinal fluid leak; skull base repair; return to the operating room